Study of dissolved copper (ii) speciation at Pulau Pangkor, Perak, Peninsular Malaysia - Godon, Edrianna; Mohamed, Khairul Nizam; Yusoff, M. K.; Surimin, A.; Gani, M. A.; Wahab, Z. A. (Forestry Department Peninsular Malaysia, 2019)
The profile of seawater samples was analyzed from a few selected stations at Pulau Pangkor, Perak for dissolved copper speciation analysis in order to determine the concentration level of toxic cupric ions (Cu ²⁺ ) in seawater. The concentration of natural organic Cu(II)-ligand binding (CuL) and its conditional stability constant (Log K’CuL) in each sample was determined by using competitive ligand exchange–adsorptive cathodic stripping voltammetry (CLE-AdCSV) method with salicylaldoxime (SA) as competitive ligand. Our present data have recorded a total dissolved Cu concentration [dCu] ranged between 3.14–7.12 nM and 3.10–9.11 nM at a surface layer and at 15-meter depth, respectively. An organic ligand concentration [CuL] at the surface layer ranges between 4.41-13.25 nM, with its conditional stability constants (log K'CuL) between 11.55-12.17. However, at 15-meter depth, the [CuL] was recorded between 5.90-11.14 nM with log K'CuL ranged 10.93-12.84. On the other hands, a free Cu ion activity, pCu (pCu = −log[Cu ²⁺ ]), was ranged from 8.97-10.35, and was slightly less compared to the pCu values that have been recorded in other coastal waters (>12). The free [Cu ²⁺ ] was ranged between 10 ⁻⁹ –10 ⁻¹¹ pM, which was slightly below the toxicity threshold (10 ⁻⁸ pM). This initial study has suggested that dCu was largely complexed by organic ligands (>99.6%), both strong organic ligand (L1: LogK>12) at surface and weak organic ligand (L2: LogK<11) at the deeper layer. The presence of these two classes of ligands have buffering the free Cu ²⁺ ions, yielding a non-toxic Cu to the microorganisms.